Assessment of heavy metal contamination and environmental risk in soils and surface waters adjacent to phosphate mining areas, Southern Iraq - Shandookh , Fatima Kareem; Abbas, Zainab M. (Brawijaya University, 2026)
Phosphate mining is a major driver of land degradation and heavy metal contamination. This study provides a comprehensive geo-environmental and health risk assessment of eight heavy metals (Pb, Cd, Cr, Cu, Zn, Ni, As, Co) in soils and surface waters surrounding an active phosphate mining complex in southern Iraq. Fifteen soil and five water samples were collected along a distance gradient of 85-3,100 m from the mining center and analyzed by inductively coupled plasma mass spectrometry (ICP-MS). Geochemical pollution indices, including the geo-accumulation index (Igeo), contamination factor (CF), enrichment factor (EF), pollution load index (PLI), and potential ecological risk index (PERI), were applied to quantify contamination severity. Cd and Pb exhibited the highest contamination factors (9.14 and 3.50, respectively), yielding a composite PLI of 2.85. The PERI of 866.5 indicated very high ecological risk, with Cd contributing over 63% of the total risk burden. Surface water at proximal sites exceeded WHO drinking water guidelines for Pb (38.5 ?g/L), Cd (4.85 ?g/L), and As (22.5 ?g/L). Non-carcinogenic hazard indices exceeded the safety threshold in children at six sites (HI up to 16.39), while carcinogenic risk from Cr(VI) and As surpassed the 10?? threshold. Principal Component Analysis identified three spatially distinct contamination clusters correlated with distance from the mining epicenter. Urgent remediation, land use restrictions, and continuous environmental monitoring are strongly recommended.